2004
DOI: 10.1021/nl049579f
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Photosynthetic Protein Molecular Complexes in Solid-State Electronic Devices

Abstract: Plants and photosynthetic bacteria contain protein−molecular complexes that harvest photons with nearly optimum quantum yield and an expected power conversion efficiency exceeding 20%. In this work, we demonstrate the integration of electrically active photosynthetic protein− molecular complexes in solid-state devices, realizing photodetectors and photovoltaic cells with internal quantum efficiencies of approximately 12%. Electronic integration of devices is achieved by self-assembling an oriented monolayer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
394
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 367 publications
(400 citation statements)
references
References 25 publications
6
394
0
Order By: Relevance
“…We have found that this class of designed peptide surfactants can stabilize not only the function of GPCR bovine rhodopsin in solution but also multiple subunits of the photosystem I (PSI) protein complex (35) on a dry surface (36,37). These peptide surfactants represent a promising approach to membrane protein crystallization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have found that this class of designed peptide surfactants can stabilize not only the function of GPCR bovine rhodopsin in solution but also multiple subunits of the photosystem I (PSI) protein complex (35) on a dry surface (36,37). These peptide surfactants represent a promising approach to membrane protein crystallization.…”
Section: Discussionmentioning
confidence: 99%
“…We used green plant PSI (35) to demonstrate that these designer short peptide surfactants can stabilize membrane proteins (36,37). PSI is a chlorophyll-containing membrane protein complex that is the primary reducer of ferredoxin and the electron acceptor of plastocyanin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A second approach outlined in this paper is artificial photosynthesis, whereby protein scaffolds localise pigments to capture solar energy in artificial photosynthetic reaction centres. The photochemistry of a reaction centre can generate electricity [7] or preferably a molecular fuel with the incorporation of an enzymatic catalyst (Fig. 1).…”
Section: Solar Energy and Photobiologymentioning
confidence: 99%